Performance Testing of Indonesian Hydrocarbon Refrigerants - N. P Tandian; A Suwono; A. D Pasek; T Hardianto; T. A Soelaiman; B. T Prasetyo; Sarwono Sarwono; Kafi'uddin Kafi'uddin (Mesin, 1999)
In conjunction with the CFC phase out, IURC-ES ITB has been concentrating its research of HC refrigerant on 'propane natural butane' (PNB) refrigerant. The test results obtained in IURC-ES ITB during the development of the PNB refrigerant showed that PNB has better performance than PIB and CFC-12. The field tests of PNB also showed the similar results. Recently, to reconï¬rm the previous test results, the performance of PNB, PIB and CFC-I2 were compared in a series of performance tests in the LTMP Serpong. The tests also show that PNB consistently has better performance compared to PIB and CFC-12. This paper also reports the current development of PNB refrigerant in IURC-ES ITB.